Mixed marriage preparation in the light of a General Decree issued by Polish Episcopate on October 8th 2019 - Dullak, Kazimierz (Prawo Kanoniczne, 2020)
After more than 30 years of applying the Instruction for the marriage preparation, it has been replaced by new General Decree of the Episcopate of Poland which has become effective on June 1st 2020. The material extent of the new document was restricted to conducting prenuptial investigation. Dynamically changing social and religious patterning enforce the need of new regulations of direct marriage preparation. It’s aimed at discerning in legal situation i.e. in exclusion the circumstances opposing to enter in marriage or to sort this by dispensation or permission by competent authority. The present study is focused on mixed marriages, in the light of c. 1086 §1 and c. 1124 CCL. It happens more and more often: entering marriages of various confessions and religions. This diversity carries various beliefs, traditions and experiences. It is necessary on the part of a minister to act with discretion, propriety and consideration; on the other side, with a care and diligence to regard the law of the Church on marriage to lead the betrothed to fruitful in God’s grace marriage on the ecclesiastical ground. To achieve this goal it is advisable to begin the investigation with a prayer and an oath of the parties regarding their truthful and correct answers. As a result of properly conducted investigation, it is time to make decision regarding not only the proper rite of a marriage (with or without a mass) but also regarding the participation of non - catholic minister, with his role precisely described. The document, long-awaited, should prove itself and suit the priests conducting prenuptial investigation. It is marked by more precise accuracy in resolving the nuances which may appear in the course of this stage of marriage preparation.